Favourable medium term outcome following hepatic vein recanalisation and/or transjugular intrahepatic portosystemic shunt for Budd Chiari syndrome. Issue 6 (20th September 2005) - Eapen, C E; Velissaris, D; Heydtmann, M; Gunson, B; Olliff, S; Elias, E
Abstract : Background: We report our experience with management of patients with Budd Chiari syndrome over the past two decades. In 1996 we described a novel approach involving recanalisation of hepatic veins by combined percutaneous and transvenous approaches. This was incorporated into an algorithm published in 1999 in which our preferred treatment for all cases of Budd Chiari syndrome with short segment occlusion or stenosis of the hepatic veins involves recanalisation of the hepatic veins by transvenous or combined percutaneous-transvenous approaches. In symptomatic Budd Chiari syndrome where recanalisation is not possible, we perform transjugular intrahepatic portosystemic shunts (TIPS) because TIPS decompresses the portal circulation directly in an adjustable way. In this series of patients with Budd Chiari syndrome treated with radiological interventions alone, we assess their medium term outcome using two independent objective prognostic indices. Methods: We retrospectively studied 61 patients with non-malignant Budd Chiari syndrome treated by radiological intervention alone in our centre. Results: Actuarial survival for the entire cohort at one year and five years was 94% and 87%, respectively. Survival of our patients with mild disease (according to the Murad classification) was 100% at one year and at five years, with intermediate disease severity 94% at one year and 86% at five years, and with severe disease 85% at one year and 77% at five years. Conclusion: Management of Budd Chiari syndrome by interventional radiology resulted in excellent medium term survival for patients in all categories of disease severity.